OPTIMASI KEMASAN PRODUK BINAAN POLITEKNIK NEGERI MALANG UNTUK MENINGKATKAN DAYA SAING DAN PERLUASAN PENJUALAN MELALUI OLEH- OLEH KUNJUNGAN DI POLINEMA - Ayu Sulasari; Ellyn Eka Wahyu; Tri Yulistyawati Evelina; Baroroh Lestari; Siti Nurbaya; Ahmad Fauzi (Jurnal Pengabdian kepada Masyarakat, 2025)
This service activity program is carried out with the aim of increasing competitiveness and expanding the marketing of superior products produced by the Malang State Polytechnic to partner villages and Polinema entrepreneurial students. This is done by providing encouragement and motivation to increase productivity through efforts to expand the marketing network. Assistance to PKM partners is provided in the form of knowledge, skills and best practices to market products as typical Polinema souvenirs. This service program is carried out together with DUWET partner villages, Tumpang sub-district, Malang district and the Malang State Polytechnic ETU Business Incubator. Apart from that, assistance and marketing access are also provided in order to increase the potential empowerment of village areas and increase business productivity so as to encourage improvements in the welfare of village communities and student businesses. The problem currently faced by partners is that partners (assisted village residents and entrepreneurial students of the ETU Polinema business incubator tenants) have production results in the form of processed products and handicraft products as well as creative industries that have the opportunity to be marketed, however, the trained partners have not been able to maximize their potential. So that superior products cannot be marketed optimally, they do not have sales access to market the resulting products to become superior products. Meanwhile, Malang State Polytechnic partners do not yet have superior products as souvenirs that Polinema colleagues can bring as typical Polinema products. The fostered partners do not yet have a good understanding of village economic development (Rural Economic Development) as an effort to improve the welfare of village communities and young Polinema entrepreneurial tenants through business development and exploiting market opportunities. Understanding the importance of packaging not only as product protection, but also as branding and product promotion media. It is hoped that good packaging will increase the value of the product to be sold.  The solution offered is to map superior products that are suitable and ready to be widely marketed as souvenirs from Polinema, design a product catalog from the mapping, design product packaging dosages as typical souvenirs from Polinema, and provide additional knowledge about the importance of optimizing product packaging. as well as marketing access for Polinema's fostered partners at events/activities held on the Malang State Polytechnic campus as well as ready stock product displays as souvenirs from Polinema.  Keywords: Community Empowerment, Social Entrepreneurship, Packaging Optimization, competitiveness.